Effects of Ocean Acidification, Hypoxia, and Warming on the Gut Microbiota of the Thick Shell Mussel Mytilus coruscus Through 16S rRNA Gene Sequencing - Ullah Khan, Fahim; Shang, Yueyong; Chang, Xueqing; Kong, Hui; Zuberi, Amina; Fang, James K. H.; Liu, Wei; Peng, Jinxia; Zhang, Xingzhi; Hu, Menghong; Wang, Youji (Frontiers in Marine Science, 2021)
Gut microbiota play a very important role in the health of the host, such as protecting from pathogens and maintaining homeostasis. However, environmental stressors, such as ocean acidification, hypoxia, and warming can affect microbial communities by causing alteration in their structure and relative abundance and by destroying their network. The study aimed to evaluate the combined effects of low pH, low dissolved oxygen (DO) levels, and warming on gut microbiota of the mussel Mytilus coruscus. Mussels were exposed to two pH levels (8.1, 7.7), two DO levels (6, 2 mg L−1), and two temperature levels (20, 30°C) for a total of eight treatments for 30 days. The experiment results showed that ocean acidification, hypoxia, and warming affected the community structure, species richness, and diversity of gut microbiota. The most abundant phyla noted were Proteobacteria, Bacteroidetes, and Firmicutes. Principal coordinate analysis (PCoA) revealed that ocean acidification, hypoxia, and warming change microbial community structure. Low pH, low DO, and increased temperature can cause shifting of microbial communities toward pathogen dominated microbial communities. Linear discriminant analysis effect size (LEfSe) showed that the significantly enriched biomarkers in each group are significantly different at the genus level. Phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) analysis revealed that the gut microbiome of the mussels is associated with many important functions, such as amino acid transport and metabolism, transcription, energy production and conservation, cell wall, membrane and envelope biogenesis, and other functions. This study highlights the complexity of interaction among pH, DO, and temperature in marine organisms and their effects on the gut microbiota and health of marine mussels.